Testing the scale dependence of the scale factor σeff in double dijet production at the LHC - Domdey, Svend Oliver; Pirner, Hans J.; Wiedemann, Urs Achim (The European physical journal. C, Particles and fields, 2010)
The scale factor σeff is the effective cross section used to characterize the measured rate of inclusive double dijet production in high-energy hadron collisions. It is sensitive to the two-parton distributions in the hadronic projectile. In principle, the scale factor depends on the center of mass energy and on the minimal transverse energy ET,min  of the jets contributing to the double dijet cross section. Here, we point out that proton-proton collisions at the LHC will provide for the first time experimental access to these scale dependences in a logarithmically wide, nominally perturbative kinematic range 10≲ET,min ≲100 GeV. This constrains the dependence of two-parton distribution functions on parton momentum fractions and parton localization in impact parameter space. Novel information is to be expected about the transverse growth of hadronic distribution functions in the range of semi-hard Bjorken x (0.001≲x≲0.1) and high resolution Q2. We discuss to what extent one can disentangle different pictures of the x-evolution of two-parton distributions in the transverse plane by measuring double-hard scattering events at the LHC.
Im Titel ist "eff" bei "σeff" tiefgestellt
Published online: 19 November 2009
Gesehen am 16.02.2023